Projeto didático de gênero como possibilidade para o ensino da língua materna e o desenvolvimento das capacidades de linguagem de alunos multirrepetentes - Marques, Renata Garcia (Universidade do Vale do Rio dos Sinos, 2014)
The present work aims to analyze new teaching possibilities for mother tongue through textual genders anchored in the methodological proposal of Gender Didactic Project (GDP) and reflect about them. Through action research, as definitions of Pepper (2005) and Wells (2009), in which the teacher assumes the researcher role, it was developed the methodological basis adopted for this research and for generation of the presented data. The studying focus of this research is divided in two moments. First, it focuses on analyzing how, from the news gender textual, the language capabilities of school failure students from the Project Moving Forward, final grades, from a public elementary school, RS, can be activated by means of activities proposed in the GDP "Profession Reporter in the Community", developed and applied by the teacher/researcher. And second, after application of the project, it is analyzed how the language capabilities were effectively actuated during the production process of the news gender of texts (initial production, final production and rewriting) of the same student, evidencing the relationship between the proposed GDP and the student’s language capabilities during the project development. Furthermore, this research also points out the digital literacy’s (social networks use) importance for teaching the mother tongue. As a theoretical anchor, in some principles of the Socio-Discursive Interactionism (SDI) from Bronckart and the textual genders study through didactic sequences, with studies from Schneuwly and Dolz. As well as the methodological proposal of Gender Didactic Project (GDP), defended by Guimarães and Kersch (2012), the literacy’s studies importance (STREET, 2010; BARTON, HAMILTON, 1998; KLEIMAN 2005/2007) and the relevance of digital literacy’s studies (Buzatto, 2009; ROJO, 2012; SOARES 2002; XAVIER, 2009;). All these theoretical constructs underlie this research to point new paths for the Mother Tongue’s teaching. The results show that the proposed Gender Didactic Project developed with school failure students students, leads the teacher to develop activities that explore the gender (news) as an object of education linked to a social practice of learners, promoting significantly the mobilization of language skills of these students.
Keywords: Projeto didático de gênero; Prática social; Capacidades de linguagem; Interacionismo sociodiscursivo; Letramento digital; Gender didactic project; Social practice; Language capabilities; Socio-discursive interactionism; Digital literacy; ACCNPQ::Lingüística, Letras e Artes::Lingüística